AMINO ACID COMPOSITION OF SOME PROTEIN FRACTIONS IN COTTONSEED AND THEIR IMPORTANCE IN THE NATIONAL ECONOMY (Modern education and development, 2025)
The article discusses the composition of amino acids, which are the main components of common proteins in seeds. Information is provided on the importance of proteins and amino acids in different cotton varieties, their solubility in water, salt, and other solvents.